Mitochondrial markers (cytochrome c oxidase subunit I and 16S ribosomal RNA) as supporting biomarkers for wild bird identification - Julián Marín-Villa; Albeiro López-Herrera; Daisy A. Gómez-Ruiz; Diana C. Restrepo-Rodas; Geraldine Sánchez-Rodríguez; Cristina Úsuga-Monroy (Veterinary World)
Background and Aim: Illegal wildlife trafficking is a critical threat to biodiversity, particularly in megadiverse countries such as Colombia. Birds, notably psittacines, are among the most targeted taxa. Morphological identification is often insufficient, especially when dealing with cryptic species or degraded samples. This study aimed to assess the utility of mitochondrial markers cytochrome c oxidase subunit I (COI) and 16S ribosomal RNA (16S rRNA) as molecular tools for species-level identification of psittacines housed at the Conservation Park of Medellín.